Digital Music Libraries: Librarian Perspectives and the Challenges Ahead - Goodchild, Meghan (CAML Review / Revue de l'ACBM, 2017)
This paper reports the results of a survey targeting current members of the Canadian Association of Music Libraries, Archives and Documentation Centres (CAML) that investigated the extent to which the current designs and structures of digital music libraries meet the needs of librarians in collecting, preserving, organizing, and disseminating diverse types of music documents. The challenges and barriers experienced in hosting digital collections are discussed. The gap between the current and ideal functionalities, as well as the future possibilities, are explored.